ACCESSIBILITY AND INCLUSION OF PEOPLE WITH PHYSICAL DEFICIENCY IN SEX PAYMENTS - Sanchez Maturana, Maria Fernanda [UNESP]; Souza Monteiro, Solange Aparecida de; Custodio, Vagner Sergio [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
This study aimed to diagnose accessibility and inclusion of people with disabilities in cabarets in Sao Jose do Rio Preto. We had hypothesized that these places despite they have business license, they don't have adaptations to include these people. What is a very important problem because of the social prejudice involving deficiencies, in many cases paid sex is an important sexual manifestation. Another hypothesis is that prostitutes are unwilling or unprepared to meet people with physical disabilities which generates a situation of exclusion. A third hypothesis is that users with disabilities use a few of these services due to the above difficulties, not making use of this leisure type. To reach the results, we applied a checklist in the cabarets, combined with a qualitative interview with prostitutes and the other with men with physical disabilities. The results were analyzed qualitatively and arranged in tables and graphs. The search resulted in 02 checklists, bringing the number of cabarets legalized in the city, as well as 17 interviews with disabled people and 10 interviews with the girls. In the first stage, neither establishments proved to be affordable. As for the interviews with men showed that 03 of them have gone to cabarets, but all reported that these establishments are not adapted, but the girls are receptive, despite the lack of information from them. From the other 14 men who have never been to cabarets, 50% showed interest in going, but imagine they are not accessible locations, however, they believe that they will be served by receptive girls, but also hope to find prejudice on the part of other customers. As for the other 50% who do not show interest in going to cabarets are justified by having fear of prejudice of people, as well as the lack of accessibility, making them insecure. From these, only 02 respondents said that if there were accessibility they would still not go. From 10 girls interviewed, 06 reported having attended these men, and they were amazing experiences, but difficult because they did not understand the sexual possibilities of the them, making it a troublesome relationship, because they did not know the limits of those customers. From 04 who never attend, only 01 reported interest in attending, however, when asked for the other 03 the main reason for rejection, mainly reported was the lack of preparation. But when asked whether if they were trained and informed about it they would change their opinion, only 01 of 03 said it would continue not answering. It was concluded that the biggest problem in these places is the physical accessibility and the lack of training of girls. This research confirms the importance of accessibility in the cabarets as sexual and leisure alternative, therefore, it was intended to demonstrate the importance of enforcement of the laws policy, and help the entertainment industry entrepreneurs to undertake actions to include people with disabilities considering the possibility of economic development, and therefore commercial sex workers, and potential users to provide and take advantage of this service with better quality.
Keywords: Accessibility; Inclusion; Cabarets